Spiritual care to people living with HIV and AIDS within the context of the Reformed Church of East Africa’s Plateau Mission Hospital (Kenya) - Chemorion, Edith Khakasa (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MTh (Practical Theology and Missiology))--University of Stellenbosch, 2009.